2021
DOI: 10.1007/s10967-021-07749-1
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and desorption experiments using stable cesium: considerations for radiocesium retention by fresh plant residues in Fukushima forest soils

Abstract: We conducted sorption experiments with stable cesium (133Cs) solution in different organic matter samples, aiming to understand the sorption of radiocesium (134Cs and 137Cs) in the initial throughfall by fresh plant residues (e.g., needles, wood, and bark from Japanese cedar trees) in the Oi horizon in forests in Fukushima. Among the organic matter samples, bark and wattle tannin sorbed relatively large amounts of Cs, whereas wood and cellulose powder sorbed small amounts. In contrast, samples containing clay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…During this long residence time, the remaining leachable fraction of 137 Cs in the outer bark 40 might have been washed away by stemflow. Furthermore, previous studies have suggested that the outer bark has higher sorption capacity for soluble metal ions, including 137 Cs 37 , 42 . Thus, even small input of outer bark to the forest floor might lead large spatial heterogeneity of 137 Cs activity concentrations and bioavailability there.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this long residence time, the remaining leachable fraction of 137 Cs in the outer bark 40 might have been washed away by stemflow. Furthermore, previous studies have suggested that the outer bark has higher sorption capacity for soluble metal ions, including 137 Cs 37 , 42 . Thus, even small input of outer bark to the forest floor might lead large spatial heterogeneity of 137 Cs activity concentrations and bioavailability there.…”
Section: Discussionmentioning
confidence: 99%
“…Leaching experiments were conducted in the following settings, modified from the work of Manaka et al . (2019, 2021) 25 , 37 ; all samples were oven dried at 70–75 °C and then crushed roughly to a diameter of < 1 cm by using scissors or a cutting mill (U-140, Horai Co. Ltd., Higashi Osaka City, Osaka, Japan; or WT-150, Irie Shokai, Chiyoda City, Tokyo, Japan). Each sample and the leaching solutions [ultrapure water or ammonium acetate (1 mol kg −1 , pH 7.0)] was placed in a polypropylene centrifuge tube at a weight ratio of 1:20, and mixed for 2 h by a reciprocating shaker at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The identification of adsorption sites on clay minerals and zeolites has been studied in the fields of material science and environmental chemistry. Understanding the adsorption mechanisms on zeolites is directly related to their performance as catalysts. The migration behavior of radioactive nuclides is dependent on the species of natural clay minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, K competes with Cs on the uptake carriers due to the similarity in chemical behavior; hence decreases Cs influx [9,22]. Other elements, like Na, Ca, Al, P may decrease Cs availability to plant [23].Moreover, increasing carbonate content in soil decreases the mobility of cesium [24].Besides, organic matter can affect cesium availability [25]. In this concern, up to 71% of the 137 Cs was found bonded to organic matter in the forest of Japan after Fukushima accident [26].…”
Section: Introductionmentioning
confidence: 99%